Bad dreams - Haden-Guest, Anthony (1981)
"Bad Dreams" by Anthony Haden-Guest chronicles the love triangle between Melanie Cain, Buddy Jacobson, and Jack Tupper, leading to Tupper's murder, Jacobson's trial, escape, and recapture. The book portrays the events leading to the crime, including the relationship dynamics and the subsequent legal proceedings. It also sheds light on the details of Jacobson's building, where he lived and where several women were tenants, and the surveillance practices employed. (Publisher)